Antagonistic Study on Streptomyces spp Isolated from Marine Fish and its Antibiogram Spectrum against Human and Fish Pathogens - Suguna, S (International Journal of Pharmaceutical & Biological Archive, 2012)
Antagonistic Study on Streptomyces spp Isolated from Marine Fish and its Antibiogram Spectrum against Human and Fish Pathogens